2013
DOI: 10.1080/07399332.2013.794461
|View full text |Cite
|
Sign up to set email alerts
|

Management of Conflicts Arising From Disclosure of HIV Status Among Married Women in Southwest Nigeria

Abstract: This study examined if disclosure to their spouses by married women living with HIV/AIDS resulted in conflicts. Fifty-seven women completed a questionnaire on conflict indicators. While 93% disclosed their status within 6 months of diagnosis, 12.3% did so through a third party. More than thirty-six percent (36.8%) confirmed that disclosure led to conflict. Although 19.3% had their conflicts resolved through a third party, 10% suffered separation. Marital status and fear of stigma significantly influence time t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…All the included studies (n=10) used quantitative cross-sectional research design [24][25][26][27][28][29][30][31][32][33], provided estimates of disclosure and information on the strategies PLWHA used for disclosure. The studies vary in their sample size, sample strategies and methods of data collection (see Table 3 Total 187…”
Section: Characteristics Of Studies On Hiv Disclosurementioning
confidence: 99%
“…All the included studies (n=10) used quantitative cross-sectional research design [24][25][26][27][28][29][30][31][32][33], provided estimates of disclosure and information on the strategies PLWHA used for disclosure. The studies vary in their sample size, sample strategies and methods of data collection (see Table 3 Total 187…”
Section: Characteristics Of Studies On Hiv Disclosurementioning
confidence: 99%
“…Okareh et al found that among HIV-positive women in Nigeria, 37% of participants reported that disclosure had resulted in partner conflict, and 20% of women reported ongoing conflict or abuse with partners as a result of disclosure [50]. Another cross-sectional survey in Nigeria found HIV-positive women experienced partner violence at higher rates after disclosure than before disclosure (55.8 and 38.3%, respectively) [5].…”
Section: Trauma and Hiv Disclosurementioning
confidence: 99%
“…Some people may experience negative consequences of disclosure such as damage to existing relationships [10], stigma and discrimination [11] as well as potential abuse [12][13].…”
Section: Introductionmentioning
confidence: 99%